Evaluation of the coordination between China’s technology and economy using a grey multivariate coupling model - Xiao, Qinzi; Shan, Miyuan; Gao, Mingyun; Xiao, Xinping; Guo, Huan (Technological and Economic Development of Economy, 2021)
As extremely complex interactions exist in the process of economic research and development, a novel grey multivariable coupling model called CFGM(1,N) is proposed to evaluate the coordination degree between China’s technology and economy with limited information. This proposed model improves the aggregation in GM(1,N) model through the Choquet integral among λ-fuzzy measure, which can reflect interactions among factor indexes. Meanwhile, it can estimate the coordinate parameters via the whale optimization algorithm and obtains the coupling coordination degree combining with grey comentropy. To verify the proposed model, a case study using a dataset from China’s technology and the economic system is conducted. The CFGM(1,N) model has a better performance in the convergence and interpretability, as compared to the three heuristic algorithm and two classical approaches. Our finding suggests that China’s technology and the economic system is still relatively coordinated. Results also reveal that there exists strong negative cooperation between the comprehensive human input and the comprehensive capital investment in this system. First published online 19 November 2020